Review and Validation of Bayesian Dose‐Optimizing Software and Equations for Calculation of the Vancomycin Area Under the Curve in Critically Ill Patients. Issue 12 (23rd November 2018) - Turner, R. Brigg; Kojiro, Kyle; Shephard, Emily A.; Won, Regina; Chang, Eric; Chan, Dominic; Elbarbry, Fawzy
Abstract : Background: Vancomycin area under the concentration‐time curve (AUC) has been linked to efficacy and safety. An accurate method of calculating the AUC is needed. Methods: Bayesian dose‐optimizing software programs available for clinician use and first‐order pharmacokinetic equations were evaluated for their ability to estimate vancomycin AUC. A previously published rich pharmacokinetic data set of 19 critically ill patients was used for validation of the AUC estimation. The AUC estimated using subsets of the full data set by Bayesian software and equations was compared with the reference AUC. Accuracy (ratio of estimated AUC to the reference AUC) and bias (percentage difference of estimated AUC to reference AUC) were calculated. Results: Five Bayesian dose‐optimizing software programs (Adult and Pediatric Kinetics [APK], BestDose, DoseMe, InsightRx, and Precise PK) and two first‐order pharmacokinetic equations were included. Of the Bayesian programs, InsightRx was the most adaptable, visually appealing, easiest to use, and had the most company support. Utilizing only the trough, accuracy (range 0.79–1.03) and bias (range 5.1–21.2%) of the Bayesian dose‐optimizing software were variable. Precise PK and BestDose had the most accurate estimates with the accuracy values of BestDose exhibiting the most variability of all the programs; however, both programs were more difficult to use. Precise PK was the least biased (median 5.1%). Using a single nontrough value produced similar results to that of the trough for most programs. The addition of a second level to the trough improved the accuracy and bias for DoseMe and InsightRx but not Precise PK and BestDose. APK did not reliably estimate the AUC with input of two levels. Using two levels, the pharmacokinetic equations produced similar or better accuracy and bias as compared with Bayesian software. Conclusion: Bayesian dose‐optimizing software using one or more vancomycin levels and pharmacokinetic equations utilizing two vancomycin levels produce similar estimates of the AUC.